I Thought I Would Wear Heels to my Wedding - Aludria Joweria, Tikia (Kampala : Tikia Aludria Joweria, 2024)
I Thought I Would Wear Heels to My Wedding is a poignant exploration of love, self-discovery, and the unexpected turns life can take. Set against a backdrop of cultural expectations and personal dreams, this stroy follows a young woman's journey through the complexities of relationships and identity.